1986
DOI: 10.3801/iafss.fss.1-97
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Sample Orientation On Piloted Ignition And Flame Spread

Abstract: An experimental investigation is conducted to study the effect of sample orientation on piloted ignition and opposed-wind flame spread. Two types of wood (red oak and mahogany) were used for the purpose and two orientations (horizontal and vertical) were investigated. In the horizontal mode, axisymmetric fire spread over wood samples was studied and the corresponding piloted ignition tests were conducted on smaller samples of the same wood. In the vertical mode, lateral flame spread and piloted ignition tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 13 publications
1
32
1
4
Order By: Relevance
“…The fact that the ignition temperature falls as the incident heat flux is reduced initially appears to conflict with Atreya et al [12] in which they found that the ignition temperature rises as the incident heat flux decreases. However on close examination of their data (for Mahogany) it was found that the minimum incident heat flux used in their experiments was ~18 kW/m 2 .…”
Section: Ignition Temperature and Incident Heat Fluxcontrasting
confidence: 49%
See 1 more Smart Citation
“…The fact that the ignition temperature falls as the incident heat flux is reduced initially appears to conflict with Atreya et al [12] in which they found that the ignition temperature rises as the incident heat flux decreases. However on close examination of their data (for Mahogany) it was found that the minimum incident heat flux used in their experiments was ~18 kW/m 2 .…”
Section: Ignition Temperature and Incident Heat Fluxcontrasting
confidence: 49%
“…Abu-Zaid & Atreya [11] considered the effect of moisture on the ignition of cellulosic materials. Further work by Atreya, Carpentier & Harkleroad [12] examined the effect of sample orientation on piloted ignition and flame spread on wood.…”
Section: Generalmentioning
confidence: 99%
“…More materials can be found in [6][7][8][9][10][11][12][13]. However, due to the limitations in the model presented here above, the applicability of the methodology has to be tested for each new considered material.…”
Section: Heat and Mass Transfer In Fires: Scaling Laws Ignitionmentioning
confidence: 99%
“…A simple model for the ignition process based on previous studies will be used here [6][7][8][9][10][11][12][13]. The following description and the equations developed in the next section can be found in [12].…”
Section: Materials Flammabilitymentioning
confidence: 99%
“…A number of previous publications have focused on critical time (Atreya et al, 1986;Babrauskas, 2001;Bilbao et al, 2002;Brescianini et al, 2003;Delichatsios et al, 2003;Moghtaderi et al, 1997;Thomson et al, 1988), heating mode (Babu and Chaurasia, 2003;Frankman et al, 2010;Lizhong et al, 2007;Tan et al, 2009), and mass loss rate (Delichatsios, 2005;Lautenberger and Fernandez-Pello, 2009;McAlister et al, 2012;Shen et al, 2006). Many of these studies were on pyrolysis and/or combustion models with an ignition criterion that utilized a critical surface temperature as the ignition temperature (Atreya et al, 1986;Bilbao et al, 2002;Frankman et al, 2010;Lautenberger and Fernandez-Pello, 2005;Thomson et al, 1988). Experiments of Atreya et al (1986) and Thomson et al (1988) showed that the critical time is approximately the same time at which the surface of the particle begins to undergo pyrolysis.…”
Section: Ignition and Pyrolysis Of Woody Wildland Fuel 781mentioning
confidence: 99%